BigTech in Finance: Benefits and Threats for the Banking Sector - Piotr NASILOWSKI (Communications of International Proceedings, 2021)
The aim of this paper is to point and evaluate key factors determining BigTech’s success in the finance sector and banks’ response to this phenomenon. The author lists main activities performed by BigTech in this area and points out potential threats and opportunities for banks’ business models that come with BigTech’s invasion into finance. The author also discusses the impact of digital transformation of banks on their future strategies and potential partnership with BigTech.
Keywords: Finance; banking; BigTech; credits